2008
DOI: 10.1159/000161880
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Thickness Can Predict Visual Outcome in Patients with Persistent Central Serous Chorioretinopathy

Abstract: Aims: To evaluate relationships between visual prognosis and foveal thickness measured by optical coherence tomography in patients with unilateral persistent central serous chorioretinopathy. Methods: Fifteen eyes of fifteen patients with symptoms for more than 6 months were evaluated on visual acuity and foveal thickness before and after foveal reattachment. Results: Mean age was 49.7 years (range 34–69), symptoms prolonged for 21.8 months (7–36), logarithm of the minimum angle of resolution (LogMAR) was 0.27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
2
17
2
Order By: Relevance
“…Foveal thickness has been occasionally reported to correlate with visual acuity in CSR [27,28,29]. However, we found that neither total central retinal thickness nor central neurosensory retinal thickness was correlated with baseline or final BCVA.…”
Section: Discussioncontrasting
confidence: 78%
“…Foveal thickness has been occasionally reported to correlate with visual acuity in CSR [27,28,29]. However, we found that neither total central retinal thickness nor central neurosensory retinal thickness was correlated with baseline or final BCVA.…”
Section: Discussioncontrasting
confidence: 78%
“…The central retina in eyes with chronic CSC is thin and correlates with disease duration based on OCT studies. 50,51 The present study also showed that the central retina in eyes with chronic and acute CSC was significantly thinner than in normal subjects. Therefore, a thinner central retina may result in a low MPOD in the affected eyes with chronic CSC for the same reason as in normal eyes.…”
Section: Discussionsupporting
confidence: 64%
“…Piccolino et al reported that the mean final BCVA was better in the preserved outer plexiform layer than in an atrophic outer plexiform layer 12. Correlation of logMAR BCVA and foveal thickness after fluid resolution in CSC ranges from −0.432 to −0.81 in the published literature 14 15…”
Section: Discussionmentioning
confidence: 99%